2006
DOI: 10.1002/icd.473
|View full text |Cite
|
Sign up to set email alerts
|

Child care before 6 months of age: a qualitative study of mothers' decisions and feelings about employment and non‐maternal care

Abstract: Employment of women while their children are infants has increased in the UK in the last decade. This study of 57 employed mothers of infants less than seven months old examined their retrospective reports of planning child care and their contemporaneous feelings about the child care they were using, based on qualitative interviews. Issues addressed included mothers' reasons for returning to employment at that time, their theoretical preferences among a range of child care types and providers and the process o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 23 publications
(39 reference statements)
2
17
0
Order By: Relevance
“…The relationship between the childcarer and the child was highlighted as being of vital importance, for all the women in this study in relation to choosing childcare; a finding that is well supported by previous research (Atkinson, 1994;Barnes et al, 2006;Cryer and Burchinal, 1997;Leach et al, 2006;Ball, 2001, 2006;Vincent et al, 2008). Nevertheless, their concept of love remained emotional and even nebulous something which Gregson and Lowe (1994) argue are the 'contradictions and tensions' involved in 'paying for love ' (p. 191); a notion which Lynch (2007) claims is non-commodifiable.…”
Section: 'Love'supporting
confidence: 87%
See 1 more Smart Citation
“…The relationship between the childcarer and the child was highlighted as being of vital importance, for all the women in this study in relation to choosing childcare; a finding that is well supported by previous research (Atkinson, 1994;Barnes et al, 2006;Cryer and Burchinal, 1997;Leach et al, 2006;Ball, 2001, 2006;Vincent et al, 2008). Nevertheless, their concept of love remained emotional and even nebulous something which Gregson and Lowe (1994) argue are the 'contradictions and tensions' involved in 'paying for love ' (p. 191); a notion which Lynch (2007) claims is non-commodifiable.…”
Section: 'Love'supporting
confidence: 87%
“…According to Barnes et al (2006) parents' explanation of their choices of childcare is largely based on hindsight. Several studies have suggested that mothers' 'ideal' childcare choices may change in line with what actually happens (Layard and Dunn, 2009;Leach, 2009;Leach et al, 2006;Pungello and Kurtz-Costes, 1999). Uttal (1996) investigated the views of 31 employed mothers and identified three main interpretations of childcare:…”
Section: An Historical Overview Of Women In the Workforcementioning
confidence: 99%
“…Convenience of location, hours of availability, and cost were key factors in families' childcare choices, more so than specific aspects of quality (Henly and Lyons 2000;King et al 2002;Leach et al 2006). The cost of care is a particular concern for those who do not qualify for childcare assistance and also cannot afford high childcare expenses.…”
Section: Childcare Decision Factorsmentioning
confidence: 99%
“…Most working parents must deal with arranging childcare; however, some parents may struggle more than others in finding the right option. Parents must consider multiple logistical factors such as the location, cost, and availability of care, along with employment factors such as work schedules and flexibility (Henly and Lyons 2000;Hofferth et al 1991;King et al 2002;Leach et al 2006). The choices available to families may not always match children's and parents' needs and preferences.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, in a qualitative study of maternal feelings about child care in the UK, Leach et al (2006) found that mothers whose infants received non-maternal care had a strong desire for open communication with the child care provider and firm control over their child's daily lives. These mothers also expressed concern over the safety of the environment their children were experiencing, as well as the amount of cognitive stimulation their child received (Leach et al, 2006).…”
mentioning
confidence: 99%